Efek berbagai pretreatment koro pedang kupas terhadap kadar HCN, proksimat dan karakteristik fisik tepung koro pedang (Canavalia ensiformis) - Rohani Islami; Endang Prangdimurti; Tjahja Muhandri; Dede Robiatul Adawiyah (AGROINTEK, 2025)
Jack bean is one of the alternative protein sources, with a protein content of 27.4% on a dry basis. The production of jack beans in Indonesia reached 12 tons/ha, with an average of 7 tons/ha. The utilization of jack bean for food was not optimal because it contained cyanide acid (HCN). For optimal utilization, jack bean must be transformed into low-HCN jack bean flour. HCN levels could be reduced to safe limits through food processing, namely by soaking and thermal treatment. The purpose of this research was to study the effect of jack bean pretreatment (no soaking, water soaking, or NaHCO3 soaking) followed by heat treatment (boiling or roasting) on HCN levels, proximate content, and physical characteristics of jack bean flour. Peeled jack bean is given a soaking treatment (without soaking, soaked in water for 24 hours, and soaked for 24 hours in NaHCO3 1%), followed by boiling for 60 minutes or roasting for 30 minutes, then dried and ground. The jack bean flours is analyzed for HCN content, water content, ash content, fat content, protein content, and carbohydrate content, as well as the degree of whiteness and aw.. This study showed that soaking treatment for 24 hours followed by boiling for 1 hour could reduce HCN levels to 4 mg/Kg, but roasting treatment could increase HCN levels in jack bean flour compared to the control. Pretreatment had a significant effect on water content, ash content, and fat content, while protein and carbohydrate levels had no significant effect. There was no difference in the degree of whiteness except for the roasting treatment, while the water activity decreased significantly in the range of 0.2-0.5 and lower than without treatment